Student perspectives on the flipped classroom concept in secondary math lessons - Bianca Wolff; Boris Girnat (Springer, 2024)
Abstract The flipped classroom concept is the reversal of the traditional teaching activities so that new content is first worked through by the learners independently and then the joint lesson time is used to practise and consolidate this content. This concept can result in didactic advantages. However, it is assumed that the concept also places increased demands on learners. As part of an intervention study with 452 participants in 15 lower secondary schools in Lower Saxony (Germany), pupils were given a questionnaire including the following items "I like this in the flipped classroom" and "I don't like this in the flipped classroom". This article analyses the answers to those questions using a qualitative content analysis. The resulting categories are analysed in more detail in a thematic analysis to identify specific aspects of the flipped classroom that the learners like or dislike. The preparation through videos, self-directed learning and adaptability of the learning speed were named particularly frequently in the positively connoted categories. The negative aspects included comprehension problems, the desire for more explanations from the teachers, time pressure, and time management problems. These results contrast with previous research results on the flipped classroom concept in higher education didactics.